2010
DOI: 10.1007/s12035-010-8111-y
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol as a Therapeutic Agent for Neurodegenerative Diseases

Abstract: Excess production of reactive oxygen species in the brain has been implicated as a common underlying risk factor for the pathogenesis of a number of neurodegenerative disorders, including Alzheimer’s disease (AD), Parkinson’s disease (PD), and stroke. In recent years, there is considerable interest concerning investigation of antioxidative and anti-inflammatory effects of phenolic compounds from different botanical sources. In this review, we first describe oxidative mechanisms associated with stroke, AD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(188 citation statements)
references
References 102 publications
5
182
0
1
Order By: Relevance
“…Furthermore, excess formaldehyde can induce amyloid or Tau protein aggregation, two of the markers of the late stages of Alzheimer's disease (Chen et al 2006;Nie et al 2007a, b). The formaldehyde scavenger resveratrol can directly decrease hippocampal formaldehyde levels (Tong et al 2011) and the numbers of senile plaques in APP transgenic mice (Karuppagounder et al 2009), although the activation of other pathways by resveratrol has not been ruled out (Sun et al 2010). These data suggest that the scavenger of hippocampal formaldehyde is a potential and beneficial therapeutic target for age-related memory decline and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, excess formaldehyde can induce amyloid or Tau protein aggregation, two of the markers of the late stages of Alzheimer's disease (Chen et al 2006;Nie et al 2007a, b). The formaldehyde scavenger resveratrol can directly decrease hippocampal formaldehyde levels (Tong et al 2011) and the numbers of senile plaques in APP transgenic mice (Karuppagounder et al 2009), although the activation of other pathways by resveratrol has not been ruled out (Sun et al 2010). These data suggest that the scavenger of hippocampal formaldehyde is a potential and beneficial therapeutic target for age-related memory decline and neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Parkinson disease (PD) is a chronic and progressive neurodegenerative disease associated with impairment of motor functions (Sun, Wang, Simonyi, & Sun, 2010). It is the second most common neurodegenerative disease and about 2% of people over the age of 65 suffer from the disease (de Rijk et al., 1997).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…This disease is an autosomal dominant disorder, and mutations in the alpha‐synuclein gene are the cause of this disease. Although environmental and genetic factors contribute to PD development, the exact etiology remains unclear yet (Gasser, 2005; Sun et al., 2010). Recent studies showed that neurotoxic agents are possible inducers of PD such as manganese (Sun, Yang, & Kim, 1993), dimethoxy phenyl‐ethylamine (Koshimura et al., 1997), paraquat (Miller, Sun, & Sun, 2007), and 1‐methyl‐4‐phenyl‐1, 2, 3,6‐tetrahydropyridine (MPTP) causing oxidative stress, and also mitochondrial dysfunction (Alvira et al., 2007) and inflammation are important factors in dopaminergic neurons degeneration in PD (Giasson, Ischiropoulos, Lee, & Trojanowski, 2002; Sun et al., 2010).…”
Section: Resveratrol and Diseasesmentioning
confidence: 99%
“…This polyphenol occurs naturally in grapes, purple grape juice and some berries such as blueberries and cranberries [39]. Resveratrol may exert protective effects through scavenge ROS produced by NADPH oxidase, activate SIRT1 [Sirtuin 1], which leads to restoration of mitochondrial function and biogenesis, and stimulation of biosynthesis of "vitagenes", and inhibit microglial activation [40]. Curcumin comes from the rhizome, or root, of the turmeric plant and is used frequently in Indian dishes [producing the familiar yellow color of curry].…”
Section: Dietary Polyphenolsmentioning
confidence: 99%